Case report: Case analysis of multiple sclerosis with preclinical systemic lupus erythematosus presenting as rare bilateral horizontal gaze palsy - Huan, Li; Xiangming, Yu (Frontiers in Immunology, 2024)
We present an analysis of a case initially manifesting as bilateral horizontal gaze palsy, eventually diagnosed as multiple sclerosis (MS) with preclinical systemic lupus erythematosus (p-SLE). The patient, a 25-year-old male, exhibited restricted movement in both eyes. Cranial MRI revealed multiple demyelinating lesions; serum analyses indicated elevated levels of antinuclear antibodies (ANA), anti-Sm antibodies, and anti-nRNP antibodies. Oligoclonal bands were identified in the cerebrospinal fluid. Neurophysiological assessments demonstrated damage to the optic, auditory, and facial nerves. Given the clinical presentation, laboratory findings, and the progression of the disease, the final diagnosis was confirmed as MS associated with p-SLE. The onset of MS with oculomotor disturbances is rare and may be easily confused with neuropsychiatric systemic lupus erythematosus (NPSLE). Furthermore, the differentiation of p-SLE from undifferentiated connective tissue disease (UCTD) in the early stages presents significant challenges. Early identification of risk factors and close monitoring of disease activity is crucial for an accurate diagnosis.